The Effect of Montessori Math Model Method in Learning Addition and Subtraction of Fractions in Grade V Pupils - Jovenil Bacatan (Indonesian Journal of Mathematics Education, 2022)
The study was conducted to determine if the utilization of Montessori Math Model Method in learning the addition and subtraction of fraction has an impact to the improvement of students’ performance. A quantitative design was used in the study. The essential data were gathered from a total number of 67 respondents, 34 students from the experimental group and 33 students from the control  group, with the aid of validated questionnaire. Data were analyzed and interpreted using the Average Weighted Mean and T-test as statistical tools. According to the findings of the study, data revealed that the result of pre-test and post-test of both experimental and controlled group is significant. The result showed that there is a significant difference of the utilization of the Montessori Math Model Method in learning addition and subtraction of fraction in Grade 5 Pupils in Kaputian Elementary School.